Cossack baroque as a state historical and cultural style: formation and dynamics of development - Pohribna, Daria (Ukrainian Cultural Studies, 2024)
Background. The crisis situation in the contemporary Ukrainian socio-humanitarian space requires reflections on cultural facts from the past, aiming to reassess their impact on the present. The purpose of the research is to analyze Cossack baroque as a state-oriented historical and cultural style and to determine the extent of its influence on the history and culture of Ukraine, as well as to reveal its relevance in contemporary society. Research tasks that are necessary for achieving this aim  relates to  identifying the preconditions for the formation and development of baroque as a Cossack state style of the 17th-18th centuries, and justification of its relevance for contemporary societal development.Methods. As a methodological toolkit are used following methods: the unity of logical and historical, historical-genetic, comparative, historical reconstruction, socio-cultural, and systemic analysis.Results. Baroque as a cultural style with its characteristic features (emotionality, dynamism, metaphoricality, complexity, grandeur) arose in Western Europe and received a creative reception in Western Ukrainian lands. However, as an authentic historical and cultural style, baroque is manifested in the Cossack-Hetman state and is a consequence of the development of the Ukrainian intellectual tradition. The Ukrainian Baroque style, which the author equates with the Cossack Baroque, became not only a reflection of the psychological and mental features of the Ukrainian people, but also an expression of the Hetmanship state idea. The Cossack elder, as the elite of Ukrainian society, was both a bearer of artistic tastes and a customer of works in the Cossack Baroque style. The artistic monuments of the Cossack Baroque combine magnificence, grandeur, dynamism, metaphoricality and accumulate state narratives. Conclusions. The Cossack Baroque phenomenon is not only a reception of the Western European Baroque, which embodies the features of the Ukrainian worldview of the 17th and 18th centuries, but also an authentic Ukrainian state style of the Hetmanship era. Preservance of the Cossack Baroque era monuments to this days testifies to the existence of a state culture in the 17th – 18th centuries, which formed the value guidelines for the development of Ukraine as a state. Based on the results of a critical analysis of the scientific works of modern cultural scholars, the author defines Baroque not only as the dominant style of Ukrainian culture, but also as the state style of the Cossak-Hetman state, which determines the greatest significance of Cossack Baroque for the history of Ukrainian culture.
Keywords: Baroque; Ukrainian worldview; Hetmanship culture; state style